MENCIPTAKAN LINGKUNGAN KAYA BACAAN BAGI ANAK TAMAN KANAK-KANAK (TK) - Mardiana, Harisa; ,, Trida; Chandra, Yopie; ,, Arnelli; Nuratriningrum, Ari (Buletin Udayana Mengabdi; Vol 23 No 6 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i06.p10, 2024)
To cultivate a lifelong love of reading and learning, our community service project embarked on a transformative journey to create a reading-rich environment for kindergarten children. The aim is to inspire a lifelong love of reading and learning in kindergarten students by creating a reading-rich environment, providing access to age-appropriate books, and prom. The implementation of the methodology came with five stages: (1) Planning to read books and choosing the location, (2) Procuring reading books and selecting reading books, (3) Reading books to kindergarten and having a dialog with children and teachers, (4) Evaluating the results provided and evaluations from school principals and teachers, (5) Donating reading books and completing community development duties. The Community Development Scheme aims to create a reading-rich environment, increasing access to age-appropriate reading materials, engaging parents and caregivers in nurturing young readers, enhancing reading skills, and celebrating reading achievements. The result positively impacted TK Perguruan Buddhi, which proved to transform the foundation for a lifelong love of learning. The impact extended beyond the classroom, as we observed parents and caregivers being inspired to foster reading-friendly home environments. It heightened parental involvement, as Voorhis et al. (2013) suggested, and laid a strong foundation for the children's future educational journeys. Additionally, the active support of our university underscored the importance of campus involvement in community development, amplifying the impact of our efforts. Keywords: Kindergarten Education, Early Literacy, Community Development Engagement, Lifelong Learning, Reading Promotion